Reconstruction of head impacts in FIS World Cup alpine skiing - Steenstrup, S. E.; Mok, K.-M.; McIntosh, A. S.; Bahr, R.; Krosshaug, T. (British Journal of Sports Medicine, 2018)
Introduction Prior to the 2013/2014 season, the International Ski Federation (FIS) increased the helmet testing speed from 5.4 to 6.8m/s for alpine downhill, super-G and giant slalom. Whether this increased testing speed reflects head impact velocities in real head injury situations on snow is unclear. We therefore investigated the injury mechanisms and gross head impact biomechanics in seven real head injury situations among World Cup (WC) alpine skiers.